Differences and Similarities for Spatial and Feature-Based Selective Attentional Orienting - Galashan, Daniela; Siemann, Julia (Frontiers in Neuroscience, 2017)
Using selective attention, we prioritize behaviorally relevant information out of all surrounding stimulation. Attention can be oriented intentionally to spatial and/or non-spatial properties (feature-based attention). When comparing spatial and feature-based attention, previous studies identified a common fronto-parietal network, although some reported specific activation for spatial attention and few found higher activation for feature-based attention. Most studies examining differences between attention types investigated the cueing epoch. We examined reorienting processing (after invalid cueing) and correctly focused attention (after valid cueing) for spatial and feature-based orienting using fMRI in two human samples with 40 participants overall and identical stimuli, stimulus probabilities, and timing for all conditions. A fronto-parietal network including parts of the ventral orienting network was activated for reorienting and focused attention for both attention types. Common activity over validities and attention types was located in bilateral IPL/SMG, bilateral IFG/insula, and the cerebellum. A network of mainly posterior areas showed higher activity for spatial compared to feature-based orienting. Conversely, no specialized areas for spatial focused attention or for feature-based attention (reorienting/focusing) was observed. The posterior clusters specialized for spatial reorienting showed overlapping activity with clusters involved in common spatial and feature-based reorienting as well as focused attention over attention types. Therefore, the results hint at a superordinate fronto-parietal network for both attention types during reorienting and focusing, with a spatial specialization of posterior sub-regions.